The churches' response to the HIV/AIDS pandemic: a case study of Christian agencies in the Cape Town area - Schmid, Maria Barbara (Department of Religious Studies, 2018)
It is two decades since the start of the HIV/AIDS pandemic. Since then it has caused the death of millions and untold suffering to many more, especially in sub-Saharan Africa. Yet, while some Christian response soon developed, until a few years ago the majority of churches have struggled to recognise in this disaster a challenge to themselves. The last few years have seen a ﬂurry of activity from churches and Christian agencies in this field. New AIDS ministries are springing up, often in a rather haphazard fashion. This study aims to establish what the response of churches and Christian groups in the Cape Town area is to the HIV/AIDS pandemic. The starting point for the response lies in the perceptions shaping the churches' AIDS discourse, since church activities are to a large degree discourse based. Hence the study starts with an investigation of the relationship between discourse and practice, paying special attention to the common metaphors and discourses used when referring to HIV/AIDS. Since the African context is crucial to the way HIV/AIDS is developing here, questions are posed to these discourses from an African point of view. The study further considers the type of programmes emerging from this discourse. A survey was conducted by questionnaire in the Cape Town area to collect information from 30 Christian service providers end denominations. The aim is to evaluate whether the response is appropriate to the needs, to our African context and to the churches' mission. It is my hypothesis that while the Christian contribution to AIDS services is valuable, it is in many respects not appropriate. To support this hypothesis the study develops criteria for an appropriate AIDS discourse, and based on that for an appropriate practical response to the HIV/AIDS pandemic. These were derived from relevant literature as well as a series of informal interviews with local AIDS activists. Finally, some pointers are given as to how the Christian response to HIV/AIDS could be developed on a solid theological foundation in order to offer a service that is more appropriate to the needs, to our African context and to the churches' mission.